Differential Urinary Microbiota Composition Between Women With and Without Recurrent Urinary Tract Infection - Huang, Lei; Li, Xiangyan; Zheng, Bo; Li, Pengtao; Wei, Dali; Huang, Chenwei; Sun, Liying; Li, Haixia (Frontiers in Microbiology, 2022)
Background Recurrent urinary tract infection (RUTI) is common and burdensome in women. Due to the low concentration or slow-growing of uropathogens in RUTI, standard urine cultures (SUCs) are often negative. Next-generation sequencing (NGS) of bacterial 16S rRNA gene is more sensitive and could be used to reveal the differential microbiota between patients with RUTI and asymptomatic controls. Methods Women (aged ≥ 18 years) with clinically diagnosed RUTI with negative SUC and age-matched women asymptomatic controls with normal urinalysis were enrolled. Their midstream voided urine specimens were collected and processed for NGS (Illumina MiSeq) targeting the bacterial 16S rRNA gene V3-V4 region. The dataset was clustered into operational taxonomic units (OTUs) using QIIME. Taxonomic analysis, alpha diversity, beta diversity, multivariate statistical analysis, and linear discriminant analysis effect size (LEfSe) for differential analysis were performed and compared between patients with RUTI and asymptomatic controls. Results A total of 90 patients with RUTI and 62 asymptomatic controls were enrolled in this study. Among them, 74.4% (67/90) and 71.0% (44/62) were successfully amplified and sequenced their bacterial 16S rRNA gene. In the alpha diversity analysis, the chao1 index and observed species index were significantly lower in the RUTI group than in the control group (P = 0.015 and 0.028, respectively). In the beta diversity analysis, there was a significant difference between the 2 groups [Analysis of similarities (ANOSIM), R = 0.209, P = 0.001]. The relative abundance of 36 bacterial taxa was significantly higher, and another 24 kinds of bacteria were significantly lower in the RUTI group compared with the control group [LEfSe analysis, P < 0.05, linear discriminative analysis (LDA) score > 3], suggesting that Ralstonia, Prevotella, Dialister, and Corynebacterium may play an important role in RUTI. Conclusion The urinary microbiota of women with clinically diagnosed RUTI were significantly different from age-matched asymptomatic controls.